PENERAPAN MODEL MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR KELAS VI UPT SPF SD INPRES PARANG KOTA MAKASSAR - Andini; A. Mulkaidah Istiqamah; Nurazmi; Wahyuni Antasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the improvement of the process and student learning Achievement Pendidikan Pancasila Payload by applying the Make a Match learning model. This research approach is a qualitative approach with the type of research is classroom action research. The focus of this research is process focus and results focus. This research was conducted at UPT SPF SD Inpres Parang, Makassar city with the research subjects being teachers and fourth grade students of UPT SPF SD Inpres Parang for the academic year 2024/2025, totaling 16 students consisting of 7 male students and 9 female students. This research was conducted in 2 cycles. Each cycle includes the stages of planning, implementation, observation and reflection. From the implementation, data were collected by using observation techniques, learning outcomes tests and documentation. The results of the first cycle of learning indicate that the indicators of success have reached the sufficient category (C) and the second cycle of learning outcomes has reached the good category (B). So it can be concluded that by applying the make a match learning model can improve the process and student learning Achievement Pendidikan pancasila Payload in class VI UPT SPF SD Inpres Parang, Makassar city.